The Erosion of Biblical Certainty - Lee, Michael J. author. aut Link
IX, 244 p.
Keywords: According to conventional wisdom, by the late 1800s, the image of Bible as a supernatural and infallible text crumbled in the eyes of intellectuals under the assaults of secularizing forces. This book corrects the narrative by arguing that in America, the road to skepticism had already been paved by the Scriptures' most able and ardent defenders.